The reform of Byzantine military and territorial organization under Justinian II - Cvetković Miloš (Zbornik Radova Vizantološkog Instituta, 2016)
This paper offers a contribution to the research of the initial stages in the evolution of the thematic system. It focuses on the role of Emperor Justinian II in the formation of the new imperial military and territorial organization. Byzantine scholars have determined a long time ago that it is Justinian II who should be credited with the founding of new military districts (themes) in Hellas and Sicily. This paper, however, suggests that the formation of the themes in Thrace and Kibyrrhaiotai could also be considered a part of Justinian’s policy. In addition, the paper aims to highlight Justinian’s role in the formation of the frontier military and administrative system (the kleisourai of Strymon and Cappadocia), as well as in the reform of military and territorial organization in the Aegean basin. By creating new army units which were not based on the Late Roman heritage, Justinian essentially abandoned the principles that the Byzantine army had previously functioned on. Finally, the paper highlights the fact that the establishment of new thematic units under Emperor Justinian II was coupled with his extensive colonization measures. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 177032: Tradicija, inovacija i identitet u vizantijskom svetu]